The Potential of Developing Beef Cattle Cluster Model Based on Food Crops and Plantation and Grazing in Muna Regency - Abadi, Musram; Hafid, Harapin; Aku, Achmad Selamet; Munadi, La Ode Muh (Pascasarjana Universitas Sulawesi Tenggara, 2021)
The development of animal husbandry is closely related to the development of an area and the carrying capacity of forage forage both in quality and quantity. Muna Regency is one of the areas that has considerable potential in the development of beef cattle, because the existence of beef cattle is still very much in demand by the community to be cultivated even though it is a side business. Muna Regency also has sufficient land and natural feed availability, so the factor of regional potential in the provision of forage and the need to meet animal feed is very important. This study aims to determine the development of a beef cattle cluster model based on food crops, plantations and grazing in Muna Regency, which is carried out for 3 months. Determination of the location in this study was carried out deliberately (purposive sampling). Data analysis used in this study includes Location Quotient (LQ) analysis, analysis of feed availability based on land availability and agricultural by-products, and analysis of the feasibility criteria for cluster model development areas. The results showed that the muna district had the potential for the development of the Beef Cattle Cluster Model Area, namely; 1) Based on Food Plants with the distribution of development areas in Kabawo, Kabangka and Kontukowuna Districts, 2) Based on plantation crops consisting of IV development areas, namely (a) Region I spread over 5 sub-districts, namely Maligano, South Wakorumba, Batukara, Pasir Putih, and Pasikolaga District; (b) Region II is spread across three sub-districts, namely Parigi, Bone and Marobo Districts; (c) Region III is spread across three sub-districts, namely Tongkuno, South Tongkuno and Lohia Districts; and (d) Region IV consists of two districts, namely Napabalano and Lasalepa Districts; and 3) The potential for the development of a beef cattle cluster model area in Muna Regency based on pasture areas is Watoputi District and Kontunaga District